Learning Motivation and Coping Stress To Online Learning Difficulties in Students - Nurussakinah Daulay; Muhammad Bagas F; Lahmuddin Lubis (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to determine: 1) The effect of learning motivation on learning difficulties in new students; 2) The effect of coping stress on learning difficulties in new students; 3) The effect of learning motivation and coping stress on learning difficulties in new students. A total of 93 new students Batch 2020 Faculty of Agriculture and Animal Husbandry Tjut Nyak Dhien University. The instrument used is a learning difficulty scale, a learning motivation scale and a stress coping scale. The data analysis used is assumption test and hypothesis test. The results show: 1) based on the assumption test, the research data proved normality, homogeneity and linearity; 2) there is a positive relationship and there is a significant influence between learning motivation on student learning difficulties during online learning, namely 51.4%; 3) there is a weak relationship and there is an effect of Coping Stress with the learning difficulties of new students which is very significant during the online learning period, which is 16%; 4) there is a positive relationship and there is an influence of Learning Motivation and Coping Stress with new students' learning difficulties during the online learning period of 58.6%.